Like, literally, dude : arguing for the good in bad English - Fridland, Valerie (Viking, 2023)
"A linguistic exploration of the speech habits we love to hate-and why our "um"s, "like"s, and "you know"s actually make us better communicators. Do you hate that you say "like" too much? Do you go over your email drafts to remove excess "so"s and "really"s? Do you wish your presentation at work wasn't so full of "um"s and "uh"s? Do you get tripped up by slang, overly familiar greetings, or new pronouns? What if these features of our speech weren't a sign of cultural and linguistic degeneration or newfangled trends that won't stick around, but rather, some of the most dynamic and revolutionary tools in our arsenal? In Like, Literally, Dude, linguist Valerie Fridland argues that our most hated or confusing speech habits shape our conception of the world and our place in it in remarkable ways. With a mix of laugh-out-loud anecdotes and expertise built over two decades of research, Fridland helps us understand the history, cultural significance, and impact of how we speak today. We are all the products of centuries of linguistic progress, and the innovation hasn't stopped in our lifetimes. Writing in an accessible style and focusing on real-life examples, Fridland explains how filled pauses benefit both speakers and listeners when they're discussing new or tough topics; how the use of "dude" can help people bond across social divides; why we're always trying to make our intensifiers ever more intense; as well as many other language tics, habits, and developments. Language change is natural, built into the language system itself, and we wouldn't be who we are without it. This book will speak to anyone who talks, empowering them to communicate dynamically and effectively in their daily lives"--